Analysis of photovoltaic mini‐grid systems for remote locations: A techno‐economic approach. (15th September 2017) - Akinyele, Daniel
Summary: This paper presents a techno‐economic analysis of photovoltaic mini‐grid systems (PMs), using a group of remote houses in 3 locations in Nigeria, as case studies. It uses a worst‐case users' load demand approach for the design and analysis of the proposed energy system, according to international technical standards. It presents detailed capacity, yield and losses, battery state of charge (SoC), reliability, users' load demand increase (Ldi), and life cycle economic analyses by using the Hybrid Optimisation for Electric Renewables (HOMER) simulation tool. The effect of 25% Ldi is also considered in the paper. The study can be used to develop a practical energy model to address the poor energy situation in those locations when they are implemented. Results indicate that PMs of 68, 76, and 61 kW can meet the users' demand of 63 500 kWh/year with an availability of 99.2% for the locations, respectively. By including a 30‐kVA diesel generator to the PMs' model, an availability of 100% was obtained, demonstrating that the issue of loss of energy supply for several days in the year due to users' Ldi and the cloudy days is being addressed. The results further show that although the hybrid energy systems have relatively higher initial capital, total life cycle and replacement costs, and the cost of energy, they achieve a higher reliability compared with the proposed PMs. The research can be useful for planning solar PV infrastructure for remote locations around the world.